Performance evaluation of downflow hanging sponge–upflow sludge blanket system for Oreochromis niloticus–Brassica oleracea aquaponic system - Limin Teng; Takahiro Watari; Mami Nagai; Nur Adlin; Penpicha Satanwat; Masashi Hatamoto; Takashi Yamaguchi (Water Science and Engineering)
Maintaining low nitrate concentrations in aquaponic systems is crucial for improving water quality and maximizing the growth efficiency of fish and vegetables. Downflow hanging sponge (DHS) and upflow sludge blanket (USB) reactors have shown potential for wastewater treatment, but their use in aquaponic systems is relatively underexplored, particularly for overall performance and efficiency. In this study, a DHS reactor was coupled with a denitrifying USB reactor in an aquaponic system comprising Nile tilapia (Oreochromis niloticus) and kale (Brassica oleracea L. var. acephala DC). The USB reactor achieved a nitrate removal rate of 80.8% ± 20.5%. The specific growth rate of tilapia was 6.11% per day from day 16 to day 30. On day 45, kale growth achieved stem lengths of (4.1 ± 1.2) cm, root lengths of (12.2 ± 6.0) cm, and leaf counts of (6.3 ± 2.0) leaves per plant. Changes in the microbial communities within the reactors positively contributed to denitrification, resulting in a nitrogen utilization efficiency of 88.3%. The DHS–USB aquaponic system effectively maintained optimal water quality and stable parameters (pH, dissolved oxygen, and temperature). It regulated ammonia levels well and achieved 80.8% ± 20.5% removal rates for nitrite and nitrate after day 10. Microbial analysis highlighted significant shifts in the microbial communities within the DHS and USB reactors, underscoring their critical roles in nitrification and denitrification. Therefore, the DHS–USB aquatic system has the potential to improve agricultural production efficiency and promote sustainable development.